San Rafael : how uncommon stakeholder alliances reduced chronic homelessness - Beckman, Sara; Springer, Susan T. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
The case examines the journey of the City of San Rafael (SR) as it took on the challenge of reducing the increasing numbers of people experiencing homelessness. Examined through the lens of an MBA graduate who was hired as the homeless outreach coordinator for the city, it follows the series of decisions the city made first to focus its efforts on the chronic homeless and second to pull together a set of critical stakeholders to create a shared focus on housing the chronic homeless. The case develops an appreciation for complexity of the homeless situation, but also for the challenges associated with having many stakeholders involved. From city employees such as the police department homeless liaison to non-profit organizations such as the St. Vincent de Paul Society and Homeward Bound of Marin, there are many people involved in different roles. In this case, those stakeholders convene to find a common goal and a way to work together to apply their collective resources to housing and supporting the chronic homeless in SR.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Homelessness; Public welfare; Community organization